The Decision Support System Determines the Level of Consumer Satisfaction with the Economy Class Rail Transportation Services of PT. KAI Medan Using the Servqual Method - Septianita Simajuntak; Dedi Candro Parulian Sinaga (DISTANCE: Journal of Data Science, Technology, and Computer Science, 2021)
The utilization of this study aims to determine the level of passenger satisfaction with the quality of service at the Medan Train Station. The population in this study were Train Passengers. The samples used in this study were 30 respondents. Methods of collecting data using questionnaires and conducting direct interviews with respondents. The method used to measure service quality is the Servqual method, with five dimensions of service characteristics, namely, physical evidence, caring, reliability, responsiveness, and assurance. From the results of data processing, it is obtained that the attributes that need to be prioritized by the station for improvement are the availability of safe and comfortable parking spaces which have the largest gap, which is -0.41. The dimension that needs to be prioritized by the station for improvement is the Tangible dimension (Physical Evidence) which has a large gapter of -0.13. Based on the analysis of the results of data processing, it shows that the level of passenger satisfaction with the quality of service at the Medan Train Station is included in the Unsatisfactory category.